The impact of mortality development on the number of centenarians in England and Wales - Leeson, G (Springer, 2016)
The world is ageing both at an individual and a population level, and population ageing is truly a global phenomenon. Life expectancies at birth have increased at the global level from 47 years in the mid-20th century to around 70 years today, and are expected to rise to 76 years by the mid-21st century. The proportion of the world’s population aged 60 years and over has increased from 8% in the mid-20th century to 12%, and by 2050 it is expected to reach 21%. The emergence of large numbers of centenarians has accompanied this development. This paper outlines this emergence historically and the likely growth in the number of centenarians in the 21st century, in particular in England and Wales, analysing mortality trends since 1840 and the rise in the number of centenarians in the 20th and 21st centuries. The number of centenarians in England and Wales increased from around 160 in 1922 to almost 12,500 by 2012, but if mortality at all ages had remained constant from 1912 to 2012, then by 2012 the number of centenarians would only have been around 720. By 2100, the number of centenarians is expected to reach around 1.4 million, but if future mortality at all ages were to remain constant, then by 2100 the number of centenarians would be around 78,000. However, if predicted mortality for those aged 55 years and over was to decrease by an additional 5% every 5 years until 2100, then the number of centenarians in England and Wales would reach around 1.8 million by the end of the century.